Control interno y la presentación de los estados financieros en las empresas de comidas rápidas - Romero Castro, Xavier Fernando (2022)
Fast food companies seek to carry out their operational and administrative processes based on empirical methods, which means that suitable instruments are not applied to examine and correct the performance of their activities in a timely manner, which could seriously affect the entity's finances. Today the goods and services offered by this type of company seek that they have quality and that their processes are carried out quickly, which is an essential factor to be able to compete with other companies in the same market, therefore it is of It is extremely important to establish and control all processes that are necessary to achieve the objectives of the company and its leaders. The problem comes when they ignore investing time, money, and effort in structuring an ideal system and seek only benefits without applying what is mentioned...........